Glycemic control, micronutrients and some metabolic enzyme activity in type 2 diabetes - Nsonwu-Anyanwu, Augusta C.; Egbe, Edmund R.; Offor, Jeremaiah S.; Usoro, Chinyere A. O. (International Journal of Research in Medical Sciences, 2017)
Background: Alterations in the metabolism of some essential micronutrients and activities of some metabolic enzymes have been reported in diabetes mellitus. These changes have been attributed to hyperglycemia and increased protein glycosylation associated with diabetes and seems to be more pronounced in poor glycemic states. The influence of glycemic control on serum levels of calcium (Ca), Iron (Fe), phosphorus (P), vitamin C, and lactate dehydrogenase (LDH) and amylase activity in type 2 diabetes were determined in this study. Methods: Fasting plasma glucose (FPG), glycated hemoglobin (HbA1c), serum calcium (Ca), Iron (Fe), phosphorus (P), vitamin C, LDH and amylase activity were determined in fifty type 2 diabetic subjects aged between 40-70 years and fifty age matched apparently healthy non-diabetic subjects in Calabar, Nigeria using colorimetric methods. Socio-demographic characteristics, anthropometric indices (body mass indices (BMI), waist to hip ratio (WHR)) and blood pressure were determined using standard methods. Data was analyzed using t-test, ANOVA and Pearson correlation analysis at p = 0.05. Results: The FPG, HbA1c, serum vitamin C, Iron and calcium levels were significantly higher and serum phosphorus lower in diabetics than in non-diabetics. Diabetics with poor glycemic control (HbA1c >8.0%) have higher serum calcium and LDH activity compared to those with good glycemic control (HbA1c <8.0%). Conclusions: Diabetes may alter the metabolism of vitamin C, Iron, calcium and phosphorus while poor glycemic control may be associated with changes in calcium and LDH activity.